Mechanistic insights into chemical and photochemical transformations of bismuth vanadate photoanodes - Francesca M. Toma (Nature Portfolio, 2016)
Metal oxide semiconductors are promising materials for solar energy capture but can suffer from stability problems. Here, the authors present a methodology for evaluating corrosion mechanisms and apply it to BiVO4, revealing chemical instabilities that are not predicted from thermodynamic considerations alone.